Implementasi Kebijakan Program Kartu Identitas Anak (KIA) di Kota Denpasar - Ni Luh Putu Janu Riana; Kadek Wiwin Dwi Wismayanti; Komang Adi Sastra Wijaya (CV. Lenggogeni Data Publishing, 2023)
Implementation is a process or an outcome in which the success of a policy implementation can be measured and seen from the process and achievement of the final goal (output) whether or not the objectives to be achieved are achieved. The purpose of this research is: To find out the implementation of the Child Identity Card program policy at the Denpasar City Population and Civil Registry Service. This research includes qualitative research. informants in this study were the Head of the Population and Civil Registration Service in Denpasar City and the people who were currently at the Office of the Population and Civil Registration Office in Denpasar City, namely 1 person from Denpasar City who registered their child on a Child Identity Card and 1 person from the Community who had not registered their child in the Child's Identity Card. The data analysis technique used in this study was descriptive qualitative text analysis. The results of the analysis show that the implementation of the MCH policy by the Department of Population and Civil Registration of the City of Denpasar is in accordance with the provisions/procedures that have been set. In terms of communication, the results of observations made by researchers found that communication was carried out in two ways, namely, in the form of direct and indirect socialization carried out by the Denpasar City Population and Civil Registration Service which was good. Abstrak Implementasi adalah suatu proses atau suatu hasil dimana keberhasilan suatu implementasi kebijakan dapat diukur dan dilihat dari proses serta pencapaian tujuan akhir (output) adalah tercapai atau tidaknya tujuan – tujuan yang ingin dicapai. tujuan penelitian ini adalah : Untuk mengetahui implementasi kebijakan program Kartu Indentitas Anak di Dinas Kependudukan dan Catatan Sipil Kota Denpasar. Penelitian ini termasuk penelitian kualitatif. informan dalam penelitian ini adalah Kepala Dinas Kependudukan Dan Pencatatan Sipil di Kota Denpasar dan masyarakat yang sedang berada di Kantor Dinas Kependudukan dan Pencatatan Sipil di Kota Denpasar yaitu 1 orang masyarakat Kota Denpasar yang mendaftarkan anaknya dalam Kartu Identitas Anak dan 1 orang Masyarakat yang belum mendaftarkan anaknya dalam Kartu Identitas Anak.. Teknik analisis data yang dipergunakan dalam penelitian ini adalah teksik analisis deskriptif kualitatif . Hasil analisis menunjukan jika Implementasi kebijakan KIA oleh Dinas Kependudukan dan Pencatatan Sipil Kota Denpasar telah sesuai dengan ketentuan/prosedur yang telah ditetapkan. Dari segi Komunikasi, hasil observasi yang dilakukan peneliti ditemukan bahwa dalam komunikasi dilakukan dua cara yaitu, dalam bentuk sosialisasi langsung dan tidak langsung yang dilakukan oleh Dinas Kependudukan dan Pencatatan Sipil Kota Denpasar sudah baik. Kata Kunci : Implementasi, KIA, Kebijakan Publik